Luke Skywalker and the treasure of the dragonsnakes - Taylor, Tom, 1978- (Star Wars adventures (Milwaukie, Or.), 2012)
In this full-color graphic novel, Luke Skywalker is sent on a mission by Master Yoda to obtain the treasure hidden in the dragonsnake's lair.